Athletics for children and adolescents - Schiffer, J. (New Studies in Athletics, 2013)
How athletics serves and develops young people is critical for the future of the sport. Success in the area of talent development will impact performances at all levels and the quality of the future`s elite stars, who are essential for attention and support required for athletics to thrive. But the quality of the experience children and adolesentshave in athletics is also important, because those who do not go on to become top performers are the number one source of the audiences, volunteers and supporters, and positive memories are great tools for keeping people close and engaged with the sport. Responsibility in this area is shared among the sport`s leaders, coaches, teachers and others who need to be aware of a wide ranging set of issues touching the realms of physiology, psychology, training science, sociology and others. The aim of this article is to provide an overview of the most prominent positions and informed thinking on the most important of these issues drawn from the current literature. The main points to be covered are: • Developmental and Physical Characteristics • Physiological Adaptations to Exercise and Training, • Ranges of Sensitivity, • Differences Between the Sexes, • The Talent Problem, • Training Issues, • Strength Training, • The Dropout Problem, • Competition.